Pengaruh Pemberian Pakan Alami Yang Berbeda Terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Mas (Chyprinus carpio) - Wahyuni Blongkod; Arafik Lamadi; Suti Suherman (Transbahasa, 2024)
Goldfish belong to the omnivorous group and are influenced by the factor of giving lemna and have a specific development rate of 2.00%. one of the obstacles to fish farming is the quality of feed that does not match what is needed for fish so that it affects the food chain in fish. This study aims to determine the feeding of different natural foods (Silkworms, Cladocera, and Magot) on the growth and survival of goldfish (Cyprinus carpio). This research was conducted at the Tatelu Freshwater Aquaculture Center (BPBAT), Dimembe District, North Minahasa Regency, North Sulawesi Province, on January 19, 2023. North Sulawesi, from January 19, 2023 to March 02, 2023. The research method was experimental using a Completely Randomized Design (CRD) with four treatments and three replications, the treatment consisted of MAS FISH (Cyprinus carpio) fed with natural food Silkworm (Tubifex sp), Cladocera, and Magot (Hermatila illuces). The fry used were 3-5 cm in size and reared in a 60x40x40 cm aquarium with a density of 20 fish/48 L of water for 42 days of rearing. The results showed that the growth rate and survival rate of goldfish (Cyprinus carpio) fry fed with natural food Silkworm (Tubifex sp), Cladocera, and Magot (Hermatila illuces).